Answer:
Simplifying
6x + -3 = 2x + 13
Reorder the terms:
-3 + 6x = 2x + 13
Reorder the terms:
-3 + 6x = 13 + 2x
Solving
-3 + 6x = 13 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
-3 + 6x + -2x = 13 + 2x + -2x
Combine like terms: 6x + -2x = 4x
-3 + 4x = 13 + 2x + -2x
Combine like terms: 2x + -2x = 0
-3 + 4x = 13 + 0
-3 + 4x = 13
Add '3' to each side of the equation.
-3 + 3 + 4x = 13 + 3
Combine like terms: -3 + 3 = 0
0 + 4x = 13 + 3
4x = 13 + 3
Combine like terms: 13 + 3 = 16
4x = 16
Divide each side by '4'.
x = 4
Simplifying
x = 4 Step-by-step explanation: \\\\\\\ hope this helped